CFD prediction and experimental visualisation of cavitation and its erosion in hydraulic valves - Sven Osterland; Jürgen Weber (Flow)
This article presents an experimentally validated computational fluid dynamics (CFD) model for localising and quantifying cavitation erosion in oil hydraulic valves using large eddy simulation (LES) turbulence modelling and the cavitation erosion indices by Nohmi. Cavitation erosion, a significant factor limiting the lifespan and performance of hydraulic valves and pumps, is challenging to simulate accurately due to factors like vapour-gas cavitation separation, cavitation model parameterisation for mineral oil and accounting for the influence of air. A test rig is shown that enables an adjustable air content, the separation of gas and vapour cavitation and optical access to the cavitating valve flow. The visualisation data from this rig was used to parametrise and validate the Zwart–Gerber–Belamri vapour cavitation model for mineral oil and to include the effect of free air, achieving excellent results. The model is used to quantify cavitation erosion load, with the cavitation indices accurately reflecting erosion location, shape and intensity as well as the damping effect of air. The simulation method is suitable for industrial use to reduce cavitation erosion in hydraulic components by optimising the flow path.